IMPLEMENTASI ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK TERHADAP SURAT KEPUTUSAN GUBERNUR BALI NOMOR 1.051/03-L/HK/2012 TENTANG PEMBERIAN IZIN PENGUSAHA PARIWISATA ALAM - Revo Handhika Juang; Eki Tri Baranti (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This article discusses the legal status of WALHI Bali in filing a lawsuit at the Bali Governor's Court regarding Bali Governor's Decree No. 1.051/03-L/HK/2012. The method used in this research is normative legal method. The focus of this research is to examine PTUN decisions with case registration number: 01/G/2013/PTUN.Dps, as well as to analyze the existence of AAUPB violations in the issuance of the Bali Governor's Decree, as well as to ensure the proper implementation of AAUPB in the preparation and issuance of the Governor's Warrant according to observations Panel of Judges in Decision No: 01/G/2013/PTUN. dps